MOLECULAR GENETIC ASSESSMENT OF THE ORAL MICROBIOME IN PATIENTS WITH ALZHEIMER’S DISEASE - Babenia, H.O.; Harashchuk, I.V.; Shnaider, S.A.; Kotova, I.O.; Khrystova М.Т.; Savvova, A.O.; Korniichuk, O.E. (World of Medicine and Biology, 2023)
According to current literature, oral microorganisms are one of the factors in the development and/or progression of Alzheimer’s disease. The aim of the study was to evaluate the qualitative and quantitative composition of the microbiome of periodontal pockets of patients with Alzheimer’s disease using the polymerase chain reaction. The frequency of occurrence of the main periodontal pathogens was determined and it was shown that Tannerella forsythia and Fusobacterium nucleatum were detected in 100 % of patients in this category. The main associations of periodontal pathogens were studied and it was found that in the largest number of subjects with Alzheimer’s disease (66.7 %) there were associations of 4 bacteria. The quantitative composition of the oral microbiota in patients with dementia was determined and it was shown that Aggregatibacter actinomycetemcomitans and Fusobacterium nucleatum had the highest quantitative composition, and Porphyromonas gingivalis had the lowest. Determination of the characteristics of the oral microbiota in patients with Alzheimer’s disease will clarify the mechanisms of dementia development and suggest appropriate adapted therapeutic and preventive measures to maintain oral health.